Private evidence for atheism - Bartolome, Aaron (Religious studies, 2023)
This article presents an argument for atheism that contains a premise stated from the first-person perspective and that is intended to rationally persuade people who satisfy certain conditions. The argument also contains a premise about what God would do, if God existed, that is acceptable to theists and is affirmed in some major monotheistic religious traditions. This article explains how the argument differs from some other familiar arguments for atheism and then discusses some critical responses to it.